Training needs of women entrepreneurs in services-based Small and Medium Enterprises (SMEs) in Kota Kinabalu, Sabah - Henry, Monica; Abdullah, Muhammad Madi; Rahman, Muhammad Sabbir (2015)
The main purpose of this study is to examine training needs of women entrepreneurs in services-based enterprises in Kota Kinabalu, Sabah by determining their adequacy of training based on type of establishment, highest academic qualification, size of enterprise and types of services to support their business activities. The proposed conceptual framework was used to test 300 women entrepreneurs who are involved in services-based economies. Overall, findings from this study indicate respondents perceived moderately on the level of adequacy of training in entrepreneurship. The moderate level of perception of participants on the aspects of sufficiency, number and type of training attended denotes that they received inadequate training. This shows that there is no significant difference in the perception of respondents based on type of establishment and highest academic qualifications on the adequacy of training of women entrepreneurs to support their business activities. This indicates that there is no difference in the way the respondents perceive the adequacy of training based on type of establishment and highest academic qualifications background. However, there is significant difference in the perception of respondents on the adequacy of training based on size of enterprise and types of services. Keywords: Training Needs, Training Needs Analysis, Training Needs Assessment, Women Entrepreneurs, Sabah